FAKTOR-FAKTOR PENENTU MINAT BERKARIER DI LEMBAGA KEUANGAN SYARIAH DENGAN SELF EFFICACY SEBAGAI VARIABEL MODERASI - Yuni Wulandari; Luqman H Hakim (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study examines the influence of knowledge of Islamic accounting, financialrewards, and labor market considerations on interest in a career in Islamicfinancial institutions. This is quantitative research with research subjects, namelystudents of the Islamic Economics study program at a public university in Surabaya,totaling 165 students. The sampling technique uses simple random sampling. Thedata collection technique used is primary data, including questionnaires andinterviews, as well as secondary data in the form of documentation. Data analysistechniques used linear regression analysis, including multiple linear regressionanalysis and moderate regression analysis (MRA), with SPSS 25 software. Theresults showed that knowledge of Islamic accounting and considerations of the jobmarket had an effect on career intentions in Islamic financial institutions. Financialrewards have no effect on career intentions in Islamic financial institutions. Selfefficacy does not moderate the influence of Islamic accounting knowledge andfinancial rewards on career intentions in Islamic financial institutions. Self-efficacymoderates by weakening the influence of labor market considerations on interest ina career in Islamic financial institutions.